Biomass integrated gasification-gas turbine combined cycle (BIG/ GTCC) implementation in the Brazilian sugarcane industry: Economic and environmental appraisal - Machin, Einara Blanco; Pedroso, Daniel Travieso; Machin, Adrian Blanco [UNESP]; Acosta, Daviel Gomez; Santos, Maria Isabel Silva dos [UNESP]; Carvalho, Felipe Solferini de; Perez, Nestor Proenza; Pascual, Rodrigo; Carvalho Junior, Joao Andrade de [UNESP] (Elsevier B.V., 2021)
This study presents an economical and environmental appraisal of the Biomass Integrated Gasification/ Gas Turbine Combined Cycle (BIG-GTCC) introduction in a Brazilian sugarcane mill to increase the mill power generation potential. The analysis considers the introduction of torrefaction technology as a pretreatment procedure for wet bagasse to settle the feeding problems experienced during the gasifier continuous operation using this powdered feedstock. The environmental impacts after integrating the BIG-GTCC technology were determined using the life cycle assessment. When analyzed for the behavior of expected annual revenue in both configurations, the implementation of gasification of the surplus volume of the plant bagasse appears as the best option from an economic and environmental viewpoint. ? 2021 Elsevier Ltd. All rights reserved.
Keywords: Torrefaction; Gasification; Bagasse; Gas turbine; Economic analysis; Life cycle analysis